Sermonario de Aviñón - Ferrer, Vicente,Gimeno Blay, Francisco M.,Mandingorra Llavata, María Luz (Universitat de València, 2019)
1. - EAN 9788491345183. - 870 p. § 2. - EAN 9788491345190. - 872 p.
Sermons